On Civic Republicanism - Kellow, Geoffrey (University of Toronto Press, 2016)
" Continuing the analysis of contemporary issues through the lens of ancient theories beyond the themes of Enduring Empire and the award-winning On Oligarchy, On Civic Republicanism explores the enduring relevance of the ancient concepts of republicanism and civic virtue to modern questions about political engagement and identity. Examining both ancient and early modern conceptions of civic republicanism, the contributors respond to the work of thinkers ranging from Plato and Aristotle to Machiavelli, Montesquieu, and Wollstonecraft. A testament to the continuing influence of the concept and the ongoing scholarly debate which surrounds it, On Civic Republicanism addresses fundamental questions regarding democratic participation, liberal democracy, and the public good. Its essays speak to the many ways in which the idea of the republic still challenges us today."